Molecular investigation of Bdellovibrio bacteriovorus envelope processes associated with bacterial predation - Banks, Emma J. (2018)
Antibiotics have been used to treat bacterial infections for nearly 80 years, however, the increasing emergence of antibiotic-resistant bacteria has now led to a significant global burden of antimicrobial resistance (AMR) and a worldwide healthcare crisis. Combatting AMR requires the complementary development of novel therapeutics. Bdellovibrio bacteriovorus is a small predatory bacterium that invades Gram-negative prey, replicates within the periplasm and then lyses the host cell. This predatory ability presents B. bacteriovorus as a potential novel antimicrobial therapeutic. In this thesis, I describe two short research projects which investigate the predatory envelope processes of gliding motility and cell wall-modification in B. bacteriovorus.